Different risk factors for multiple and unifocal gliomas: a comparative study of radiological, pathological and clinical characteristics - Feng, Limei; Shi, Xinyao; Zang, Yuying; Chen, Xuzhu (Frontiers in Oncology, 2025)
BackgroundThis retrospective study compared two types of gliomas and two subtypes of multiple gliomas.MethodsThe clinical manifestations, magnetic resonance imaging (MRI) findings, pathological characteristics, and clinical outcomes of 188 patients with unifocal and 94 patients with multiple gliomas (59 with multifocal and 35 with multicentric gliomas) were analyzed.ResultsCompared with patients with unifocal glioma, those with multiple gliomas were older (P=0.001) and more likely to be male (χ2 = 4.857, P=0.028). Patients with multiple gliomas had smaller extent of surgical resection (χ2 = 161.016, P<0.001) and a worse prognosis (χ2 = 43.733, P<0.001) than those with unifocal gliomas. Multiple gliomas were more likely to have a non-superficial location (χ2 = 51.758, P<0.001), obvious peritumoral oedema (χ2 = 9.688, P=0.008), intense enhancement (χ2 = 24.547, P<0.001), a higher WHO grade (P=0.001), a lower ratio of isocitrate dehydrogenase (IDH) mutation (χ2 = 51.770, P<0.001), and codeletion of 1p19q (χ2 = 8.637, P=0.003). Tumor location and IDH status were identified as independent risk factors for multiple gliomas (P<0.001 and P=0.003, respectively). Deep tumor location was found to be the only factor related to unfavorable overall survival (OS) in multiple gliomas. Patients with multifocal gliomas were more likely to be male than patients with multicentric gliomas (χ2 = 6.521, P=0.011). The locations of multifocal and multicentric gliomas were significantly different (P=0.048). WHO grade was identified as an independent prognostic factor (P=0.034) in patients with multicentric gliomas but not in those with multifocal gliomas.ConclusionsThe demographic characteristics, extent of resection, radiological features, pathological features and prognostic factors differ between patients with multiple gliomas and those with unifocal gliomas. The clinical and radiological features differ between patients with different subtypes of multiple gliomas. Multiple gliomas located only in superficial regions are more likely to be multicentric gliomas and the prognosis is solely related to the WHO grades, providing valuable guidance for clinical treatment.